Direct encapsulation of Sm single crystals inside carbon nano-onions by pyrolysis of Tris(tetramethylcyclopentadienyl) samarium (III). (June 2019) - Boi, F.S.; Zhang, X.; Borowiec, J.; Medranda, D.; Wang, S.; Yan, K.; Zhang, J.; Wen, J.
Abstract: Multilayer fullerenes (carbon nano-onions [CNOs]) have recently attracted important research interest because of their high chemical stability that allows the encapsulation of specific materials of interest and their protection from the external environment. Until now, CNOs have been filled with numerous crystals such as Sn, Pb Fe, Co, Ni, Cu, Fe3 C, FePd3, Fe7 C3, Fe5 C2, FeCo, CoFe2 O4, and others. However, to the best of our knowledge, no reports have yet shown the direct encapsulation of pure samarium (Sm) into these structures. The encapsulation of samarium within CNOs is expected to have an important impact toward applications of these systems in biomedicine and energy storage. In this work, we show a novel synthesis method that can allow the direct encapsulation of Sm single crystals inside CNOs. These structures are obtained by sublimation and pyrolysis of a not previously used hydrocarbon precursor, namely Tris(tetramethylcyclopentadienyl) samarium (III). The electrochemical performances of these structures are also demonstrated. Highlights: Carbon nano-onions (CNOs) are molecular-like structures consisting of closed carbon shells. A novel synthesis method for direct encapsulation of samarium (Sm) single crystals inside CNOs is shown. Pyrolysis of Tris(tetramethylcyclopentadienyl) samarium (III) is demonstrated. Electrochemical performances of Sm/CNOs structures are also demonstrated.